Evaluation of an Iranian ELT book series - Nasrin Sedaghatgoftar (International Journal of Education and Learning, 2022)
Evaluating textbooks to ensure their efficacy and consistency with the course objectives is imperative as they are considered as pivotal components in English language teaching. The present study was an attempt to analyze and evaluate a local Iranian ELT book series taught at the adult department of Iran Language Institute (the ILI). In doing so, 60 English language teachers teaching English at the ILI for at least three years were invited to check their opinions on each item of the Nativized Checklist to Evaluate General English Course Books in Iran developed by Shatery and Azargoon (2012) who adapted and validated Joshua Mickley’s Checklist (2005) for the Iranian context. The design of the study was descriptive, and the data obtained were subjected to descriptive statistics to determine the frequency and percentage of the participants’ responses. The findings revealed that, generally speaking, the participants held a negative standpoint toward the content of the books. It was concluded the books need thorough modification and change. More elements of communicative language teaching need to be implemented and incorporated into the books and they need to get closer and closer to the real-world needs of the learners. Besides, more cultural elements should be provided to reinforce the learners’ cultural awareness and understanding of the target language. The findings have implications for materials developers, syllabus designers and language teachers.